THE UNENDING TRAGEDY- MATERNAL NEAR MISS WITH INTRA-UTERINE FETAL DEATH DUE TO DOMESTIC VIOLENCE IN PREGNANCY - A CASE REPORT - ESIKE, CHIDI OCHU UZOMA (Jour Med Resh and Health Sci, 2020)
ABSTRACT Domestic violence is an unfortunate but unending global tragedy that had inadvertently been tolerated globally. Pregnancy confers huge vulnerability on the woman when she is subjected to domestic violence because domestic violence that cannot kill a non-pregnant woman can kill, not just the same woman when pregnant, but may also kill her baby. The world has not done enough to protect this vulnerable group, the pregnant woman and her baby from the avoidable morbidity and mortality as some of the victims as in this case die without the appropriate laws of the land being implemented to punish the perpetrators. We report a case of domestic violence that nearly led to maternal mortality and led to intra-uterine fetal death with the perpetrator walking the streets very freely with not even a cowardly wimp or rebuke from the law.